Cultural and historical research of Nītaure manor - Zilgalvis, Jānis (Landscape Architecture and Art, 2023)
The manor of Nitaure (Nitau) is located in Cesis County, where the roads to Riga, Sigulda, Piebalga and Ieriķi meet. The village of Nitaure began to develop only after 1887, when separate plots of land were separated from the manor for residential purposes. This time, however, the subject of research is the manor house and its owners, as well as the park, which, tidy and well-kept, delights not only the local residents. The history of the manor is closely linked to the von Fermor and von Stenbock-Fermor families. Research into the history of the manor is topical, as it is rich in events that have taken place throughout the ages. There is also a lot of evidence in the archives and other historical material.